PENGARUH PEMBELAJARAN SISTEM KOLOID DENGAN MENGGUNAKAN MACROMEDIA FLASH TERHADAP HASIL BELAJAR DAN RETENSI HASIL BELAJAR SISWA KELAS XI IPA SMA NEGERI 1 TAPA (Suatu Penelitian di Kelas XI IPA SMA Negeri 1Tapa TP 2008/2009) - Salila, Musrin; Pikoli, Masrid; Suleman, Nita (Jurnal Entropi, 2009)
Colloid system [is] a[n mixture form which its [of] located nya [among/between] suspense and condensation ( harsh mixture). Name of colloid given by Thomas Graham in the year 1861. That term Come from yunani Ianguage, that is \